2022
DOI: 10.3389/fenvs.2022.993833
|View full text |Cite
|
Sign up to set email alerts
|

Research on the impacts of dual environmental regulation on regional carbon emissions under the goal of carbon neutrality-the intermediary role of green technology innovation

Abstract: As an important means to promote regional low-carbon development, environmental regulation has great theoretical and practical significance for achieving the goal of carbon-neutral development in China. Based on the panel data of 30 provinces and cities in China from 2005 to 2019, this paper first uses the intermediary effect model to analyze the impact of the implementation of environmental regulation policies on regional carbon emissions, discusses the relationship between environmental regulation, green tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In addition, these innovations upgraded the industrial structure in the cities, which consequently reduced CO 2 emissions. Using city-level data from 30 Chinese provinces from 2005-2019, Dong et al [43] showed that regulations and green technologies helped reduce emissions in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, these innovations upgraded the industrial structure in the cities, which consequently reduced CO 2 emissions. Using city-level data from 30 Chinese provinces from 2005-2019, Dong et al [43] showed that regulations and green technologies helped reduce emissions in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these studies did not distinguish between the types of environmental regulations, let alone consider the synergistic effects of different environmental regulation types. Research has also shown that environmental regulations indirectly impact industrial structure upgrading through the location selection, scale, and mode of foreign direct investment [ 30 , 31 ]. Yuan and Xiang found that in the long run, environmental regulations increase energy efficiency but hinder labor productivity in the manufacturing industry, thus not providing any favorable support for the “strong” version of the Porter hypothesis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that environmental regulations can effectively improve efficiency and reduce carbon emissions' intensity [15]. Specifically, environmental regulations reduce carbon emissions through the mediating role of green technological innovation [16]. In addition to carbon emissions, environmental regulations have ameliorative effects on industrial solid waste [17] and haze pollution [18].…”
Section: Literature Review 21 Environmental Regulation Performancementioning
confidence: 99%